Breeding behaviour of captive Shovelers - McKinney, F (Wildfowl, 1967)
The breeding behaviour of fur-winged Shovelers was studied in flight pens measuring 0.15 and 0.19 acre during five seasons. Thirty-one pairs were observed, mostly in groups of four pairs per pen. Only three pairs failed to breed, but hatching success was poor and few ducklings were raised to maturity After introduction to the pen, usually in early May, pairs were sociable for a few days but soon established well defined territories. Females began inspecting nesting cover, during the first few hours after dawn, as early as 27 days before laying. Time spent in cover each day increased on the days before laying and continued to increase during laying. Copulations were frequent in the pre-laying period but decreased during laying and were rare during incubation. Pairs often copulated twice each day before laying began, but no clear preference was shown for certain times of day. Most mountings resulted in apparently successful copulation (120 records); some males slipped off before intromission (10 records); in 15 cases, pairs were interrupted by the approach of other birds. Apparently successful rape of strange females was seen only four times. Pairs made flights around the pen and some females gave Persistent Quacking during May, but both activities stopped as soon as egg-laying began. Visits to the nest for laying were usually in the morning. Eggs were laid at a rate of one per day, but sometimes a day was skipped. Incubating females left the nest most often in late morning or in the afternoon, but there was much variation. The number of eggs decreased in many nests during incubation. There was no evidence of predation. Three observations of females flying from the nest carrying an egg in the bill suggested that this behaviour accounts for the disappearing eggs. The eggs seemed to be pierced and carried in the tip of the bill, but whether the eggs removed were addled, and how they became broken is unknown. There is no evidence that Shovelers remove the shells from which ducklings have emerged. Chasing activities peaked in frequency just after dawn and were followed by a period of sleeping during the middle and late morning. On some days there appeared to be a second peak in the number of birds sleeping in the afternoon. Chasing and sleeping were infrequent in the last hour or so before sunset, probably because feeding activity increased at that time. Seasonal and daily patterns of activity in the flight pens agreed with what is known of schedules in the wild, but the captive conditions had serious effects on breeding success. Brood behaviour was most strikingly influenced by the crowding and restriction of movement. Females with broods attacked strange ducklings and probably killed some. But the high duckling losses were likely caused mainly by shortage of preferred food in the pens.